The effect of skills acquired abroad by return migrants on social relations and quality of life in Cameroon - Gislain Stéphane Gandjon Fankem; Dieudonné Taka; Sévérin Tamwo (African Governance and Development Institute (AGDI), 2023)
This article fills the lack of work on the link between return migration and social cohesion in the country of origin of migration. For the first time, we assess the effect of skills acquired abroad by return migrants on social relations and quality of life in Cameroon using original survey data from the Institute of Demographic Training and Research. The main results, based on a probit model, show that formal and informal competences acquired abroad reduce the likelihood that return migrants will improve social relations and increase the probability that they will increase quality of life in their home country. These results remain robust to the inclusion of return migrants from African and non-democratic countries. Correcting for the endogeneity of skills acquired abroadby two-stage probit model with instrumental variablesdoes not alter these conclusions. Our results seem to corroborate the hypothesis that migration contributes to the transfer of norms and practices from destination countries to countries of origin.
Keywords: F22; O55; C3; 330; Return migrants; skills; social relations; quality of life; Cameroon